Perancangan Sistem Informasi Akuntansi Penjualan Yoghurt Pada Koperasi Peternakan Sapi Bandung Utara dengan Menggunakan Microsoft Visual Basic 2005 dan MySQL Berbasis Client Server - Ai Suryati; Dony Waluya Firdaus (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2017)
Koperasi Peternak Sapi Bandung Utara (KPSBU) is a cooperative engaged in the business of dairy farmers who process milk into yogurt. Authors conducted a study on the marketing administration in making yogurt sales report still uses Microsoft Excel as a data processing. Based on these problems the authors take the title "Design of Accounting Information Systems Yogurt Sales in North Bandung Cattle Farmer Cooperatives Using Microsoft Visual Basic 2005 and MySQL-Based Client Server 2005â€ Design research is a design study with the primary data/secondary, the type of research used academic research, methods of research used field survey techniques and literature, the development model of the system used in the output-oriented methodologies, processes and data. Structures used system development iterations. The design of the information system used context diagrams, data flow diagrams, and flowcharts.